Anthropocephalometric Aspects of Frontoethmoid Encephalocele Patients - Parenrengi, Arifin (Folia Medica Indonesiana, 2018)
Frontoethmoid encephalocele (FEE) causes maxillofacial structural abnormalities and also covers some bony landmarks, especially in the glabella region. This study examined the faces of frontoethmoid encephalocele patients before undergoing corrective surgery with the aim of identifying and assessing their facial morphological differences. This was a cross-sectional study from January 1, 2016 to June 31, 2017. A simple anthropocephalometric measurement was performed on the patient's face who would undergo surgery. Periorbital and mid-face measurements showed differences between the patients and normal groups. The midface structure of the patients clearly changed. The age when the procedure was taken also had effect. Preoperative 3DCT is proposed to describe the facial anatomy of EFE patients. Further studies in this field are suggested to produce a comprehensive database of facial morphology changes in FEE populations, both pre- and post-operatively, with the intention of producing a redefinition of FEE cases based on anthropo-cephalometric principles.